2016
DOI: 10.1158/1078-0432.ccr-15-1855
|View full text |Cite
|
Sign up to set email alerts
|

Are Doses and Schedules of Small-Molecule Targeted Anticancer Drugs Recommended by Phase I Studies Realistic?

Abstract: Tolerability of molecularly targeted agents (MTA) used in cancer therapeutics is determined in phase I trials. We reviewed the reported incidence of toxicity in phase III trials at doses and schedules recommended by phase I trials to evaluate whether these recommendations are realistic when drugs are used in larger populations of patients. We systematically reviewed a safety profile of small molecule (SM-MTA) and mAb MTA (MA-MTA) approved by the FDA in the last 12 years. There was a significantly increased per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…24,25 The apparent relationship between the clinical benefit and MTA dose level was not determined in some studies owing to probably faulty determination of RP2D 26,27 A study reported that phase 1 MTA trials have probably underestimated toxicity in dose recommendations. 28 However, another study suggested that there are clinical benefits of improved response and overall survival with increasing doses in phase 1 MTA trials. 29 To address this controversial issue and to improve the selection rates for true RP2D, efficient utilization of RDI over the long term should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 The apparent relationship between the clinical benefit and MTA dose level was not determined in some studies owing to probably faulty determination of RP2D 26,27 A study reported that phase 1 MTA trials have probably underestimated toxicity in dose recommendations. 28 However, another study suggested that there are clinical benefits of improved response and overall survival with increasing doses in phase 1 MTA trials. 29 To address this controversial issue and to improve the selection rates for true RP2D, efficient utilization of RDI over the long term should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Roda et al . reported that dose reductions were prevalent for 34 recently approved targeted agents 14. Seven of these approved agents required dose reductions in more than 50% of patients.…”
Section: Current Challengesmentioning
confidence: 99%
“…This may result in identification of a dose that is tolerable in Cycle 1 but requires reduced doses or discontinuations in a large number of patients in subsequent cycles due to delayed toxicities, resulting in patients unable to derive meaningful benefit from treatment 16. Approaches have been published where a phase Ib dose expansion cohort can be better designed to inform the recommended phase II dose (RP2D) 14. The proposal includes identifying a dose tolerable in 12–20 patients with longer observations (at least in two cycles), which results in dose reductions in less than 30% of patients.…”
Section: Current Challengesmentioning
confidence: 99%
“…However, as observed in several recent serious postmarketing safety events in Japan, there are growing concerns regarding the appropriateness of approved doses in general as well as doses for each region . Due to strategic reasons, the recommended dose is commonly optimized for use in the United States, the world's largest market where the majority of clinical development projects are conducted .…”
mentioning
confidence: 99%